Strategi Lintas Media dalam Visualisasi Kebijakan APBN: Studi Kasus Konten Karikatur dan Video di Instagram oleh Tim Kreatif Kementerian Keuangan - Iga Trisna Purnama Dewi Ningrat; Aryo Subarkah Eddyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the cross-media communication strategy employed by the Creative Team of the Public Communication and Information Services Bureau (KLI) of Indonesia's Ministry of Finance in delivering fiscal policy information via Instagram. Using a descriptive qualitative approach and case study method, the research analyzes two types of visual content—namely the caricature “APBN Bisa Yura” and the video “Rapor Bulanan #UangKita.” The focus lies on examining the pre-production to post-production stages, and how complex policy narratives are transformed into accessible, visually engaging formats that are algorithmically adaptive and psychologically resonant with digital audiences. Findings indicate that the effectiveness of content does not solely depend on visual aesthetics or engagement metrics, but on the integration of mini-research, strategic visual element selection, and systematic use of platform insights. The results demonstrate that institutional visual communication has evolved into a complex, data-driven creative process, where public policy meaning is constructed and distributed across multiple media platforms. This research contributes novelty in three major aspects: (1) a focus on internal governmental actors in developing visual communication strategies; (2) the application of data and algorithm-driven approaches within institutional creative workflows; and (3) a deep examination of the full visual content production cycle within a governmental context. Moreover, the findings affirm that the Ministry of Finance’s visual communication practices are deeply shaped by mediatization—the integration of media logic into institutional processes—as a strategic response to a highly visual and competitive public communication landscape.